Significados que construyen sobre la violencia intrafamiliar un grupo de personas remitidas por comisaria de familia al Centro de Atención psicológica (CAP) de la Universidad Antonio Nariño (UAN) (2017)
The present paper constitutes an investigation into the meanings of intrafamily violence in a group of people who attend the Centro de Atención Psicológica (CAP) of the Universidad Antonio Nariño (UAN) Sent by family stations for domestic violence. This aims to characterize the meanings given by participants to violent behavior within the family. From a historical hermeneutic paradigm with a qualitative approach Seven participants were convened to conduct interviews that were built on the three concepts that constitute the notion of meaning Context, culture and symbol; Which were codified and grouped generating eleven categories Legacy and Transmission, Family and social referents as justification for violence, Models and aggression, Role and intervention in the face of aggression, Domination, Functionality, Authority, Rational judgment, Role assigned to gender, Alcohol Consumption and Incitement. Concluding that the meaning assigned to intrafamily violence is a form of expression of their low emotional control Which occurs when they feel provoked by the other, who breaks the limits of respect that he considers fundamental Acting in a violent manner in order to maintain control and power within the family Trying to reestablish the norms and limits implicitly established by the head of the household.